The Role of Customer Satisfaction on Influence Servicescape on Word of Mouth at A Restaurant at A Zoo in Gianyar Regency - I Nyoman Murjana; I Putu Utama; I Ketut Surata (Green Publisher Indonesia, 2025)
The rapid growth of Bali’s culinary industry, particularly in Gianyar’s zoo restaurants, underscores the need to understand how servicescape dimensions influence customer satisfaction and WOM. Despite existing studies on servicescape, limited research addresses zoo-based dining contexts. This study analyzes (1) the impact of servicescape on satisfaction and WOM, (2) satisfaction’s mediating role, and (3) the most influential servicescape dimensions. A quantitative survey of 30 respondents from four zoo restaurants in Gianyar was analyzed using Structural Equation Modeling (SEM) via AMOS. Servicescape significantly boosts satisfaction (path coefficient: 0.492) and WOM (0.302), with satisfaction partially mediating this relationship (Sobel test: 4.1697, *p* < 0.05). Signs/symbols/artifacts had the strongest influence, while ambient conditions were the least impactful. The findings guide zoo restaurants in prioritizing thematic design and functionality to enhance satisfaction and WOM, offering novel insights for niche hospitality settings.